PEMANTAPAN KETAHANAN NASIONAL NKRI MELALUI PENDEKATAN KEBAHASAAN STUDI KASUS : Masyarakat Perbatasan di Batam - Tri Sulistyaningtyas (Jurnal Sosioteknologi, 2008)
An appropriate step to maintain national resilience & unity of the NKRI is by linguistic approach. In this case, the frontier community on Batam island. The basic assumption is to analyze their language, then, characteristic of the speakers might be acquired. By understanding their language, enables a strategy to be carried-out properly in guiding & socializing bahasa Indonesia to encourage awareness of nationalism & patriotism. This research-based theory consists of at least three scientific-fields. First a theory which relates to linguistic (especially sociolinguistic). Secondly, sociological-anthropology (essentially cultural). Finally the third is science of communication (particularly dynamic-communicatiion).